An Extended Tropospheric Scintillation Model for Free Space Optical Communication Systems - John O. Famoriji; Yekeen O. Olasoji; Michael O. Kolawole (IAES Indonesian Section, 2014)
Fluctuations caused mostly by tropospheric scintillation at the free space optical receiver end have been a major problem in the rapid development of telecommunication and the increasing demands for larger bandwidth is forcing the use of free space optical (FSO) technology. This paper examined existing tropospheric scintillation models of Karasawa, Van de Kamp model, Otung, Ortgies and ITU-R, and discovered that all of them operate at the microwave range, which limits their application in FSO laser beam technology that operates in PHz frequency-range. ITU-R model was later selected owing to its global application and modified for use in FSO communication system. The new model can serve as basis for communication engineers to use as platform in the link budgetary for planning and design of low margin systems of free space optical communication link.